PECULIARITIES OF INCIDENCE OF DIGESTIVE HYDROLASES OF THE STOMACH AND PANCREAS IN CHRONIC VIRAL HEPATITIS WITH С - Azimovna, Zhuraeva Mohigul; Alexseevic, Aleinik Vladimir; Mixaylovna, Babich Svetlana; Kozimzhanovna, Yakkubekova Mavluda; Abdumominova, Yusupova Nodira; Sobirjonova, Xalikova Dilrabo; Dichod kizi, Ashuralieva Nilufar (International Journal of Psychosocial Rehabilitation, 2020)
– A comprehensive assessment of the state of the pancreas in the group of patients with chronic viral liver lesions revealed a violation of the functional state of the organ in 80% of cases with chronic hepatitis and in 96.3% of cases with cirrhosis [4.6].With combined infection with hepatitis B and C viruses, more pronounced changes in the blood proteinase activity (trypsin and kallikrein activity), a more distinct decrease in antitryptic activity are noted.Exocrine pancreatic function in patients with hepatitis was also more impaired, which was manifested in some studies by a decrease in basal and stimulated secretion, enzyme secretion (especially trypsin and amylase) and bicarbonate production [4,6], in others - by an increase in amylase and lipase activity . Violations of external secretion increase with increasing severity of the main clinical and biochemical syndromes. The content of glucagon and somatostatin in the blood of patients with chronic hepatitis is increased.